The Effect of Extrinsic Motivation in Improving Employee Performance - Kadek, Yulia Saraswati Ni; Made, Yusmini Ni; Ida, Yuliantari Pande Putu (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the influence of salary and work environment in improving employee performance at PT. Pos Indonesia Gianyar Branch, using Herzberg's Grand Theory of Two Factors and Supporting Theory of Human Resource Management. Applied theory of salary, work environment, and employee performance. The method in this study uses quantitative methods and questionnaires with a population and sample of 65 respondents using saturated sampling techniques with three hypotheses. The data analysis method in this study uses multiple linear regression analysis, determination coefficient analysis, t-test (partial) and f-test (simultaneous) using the IBM SPSS version 29 program. The results of the study found, salary variables have a positive and significant effect partially on employee performance. Work environment has a positive and significant effect partially on employee performance. Salary and Work environment have a positive and significant effect simultaneously on employee performance. The implications of this study produce salary, work environment and employee performance at PT Pos Indonesia are quite moderate.